2015
DOI: 10.1038/srep14828
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic passive margins: another way to break up continents

Abstract: Two major types of passive margins are recognized, i.e. volcanic and non-volcanic, without proposing distinctive mechanisms for their formation. Volcanic passive margins are associated with the extrusion and intrusion of large volumes of magma, predominantly mafic, and represent distinctive features of Larges Igneous Provinces, in which regional fissural volcanism predates localized syn-magmatic break-up of the lithosphere. In contrast with non-volcanic margins, continentward-dipping detachment faults accommod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 51 publications
3
97
0
Order By: Relevance
“…The petrology and geochemistry results of the lava flows from ODP Hole 642E also show evidence of continental contamination (Abdelmalak, Meyer, et al, ; Meyer et al, ) that cannot easily be explained by the presence of a shallow serpentinized mantle lying just underneath the subaerial lava flows. In a similar tectonic setting (Uruguay volcanic margin), Clerc et al () showed evidence that the continental lower crust is most likely preserved underneath the SDR and adjacent basins and also confirm that volcanic margin and magma‐poor margins show striking differences (e.g., Clerc et al, ; Franke, ; Geoffroy et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…The petrology and geochemistry results of the lava flows from ODP Hole 642E also show evidence of continental contamination (Abdelmalak, Meyer, et al, ; Meyer et al, ) that cannot easily be explained by the presence of a shallow serpentinized mantle lying just underneath the subaerial lava flows. In a similar tectonic setting (Uruguay volcanic margin), Clerc et al () showed evidence that the continental lower crust is most likely preserved underneath the SDR and adjacent basins and also confirm that volcanic margin and magma‐poor margins show striking differences (e.g., Clerc et al, ; Franke, ; Geoffroy et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…This SDR wedge broadens southward up to 40 km at 75.2°N, where it is subdivided into two wedges. The individual wedges may be bounded by landward dipping faults (Figure ), as proposed in the general concept by Geoffroy et al (). The SDRs correspond widely to a negative magnetic polarization (Figures and ) and are clearly located landward of magnetic chron C24n.3n (C24B; cf.…”
Section: Interpretation and Resultsmentioning
confidence: 99%
“…Pálmason () then showed that the geometries of the Iceland Tertiary lava pile could be predicted by a kinematic model of plate crustal accretion, using lava production rate and extrusion geometries. However, recent fault‐controlled models have suggested that SDRs form during the tectonic thinning of heavily intruded continental crust and within oceanward‐dipping half grabens (Figure a; Geoffroy, ; Geoffroy et al, ). Quirk et al () propose a different fault‐based model where planar SDRs form in the hanging wall of a large‐offset normal fault in continental crust and younger convex‐upward SDRs are extruded above sheared gabbros and terminate against an axial horst composed of heavily intruded continental crust (Figure b).…”
Section: Introductionmentioning
confidence: 99%